Analisis Pengelolaan Manajemen Pembiayaan pada Pendidikan Anak Usia Dini di Tadika Anakku Sholeh, Malaysia - Rialdha Ismadillah; Alfi Amalia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the financing management of early childhood education in Tadika Anakku Sholeh Malaysia. The main focus of this research is to identify sources of financing, cost planning, and the effectiveness of financial management in supporting the educational process. The research method used is a qualitative approach with the collection of interviews, observations, and documentation. The results of the study show that the management of financing management goes through three stages, namely: financing planning, financing implementation, and financing evaluation. The three stages above cannot be separated because they are interrelated with each other. The Anakku Sholeh kindergarten school shows that the main source of financing at Anakku Sholeh Kindergarten comes from parental contributions. Even with minimal costs or financing obtained only from dues or tuition fees, this kindergarten can carry out an effective financing management strategy so that the operations in the school can run smoothly until now and the funds are allocated for school operational needs, salaries of educators, and the development of facilities and curriculum.